Evaluation of the Larvicidal Activities of the Crude Root Extracts of Ixora Coccinea L (Rubiaceae) on Aedes Aegypti Larvae - Lambert, Okwubie; Sophia, Ajogwu Amarachi (Asian Journal of Pharmaceutical Research and Development, 2021)
In this study, the larvicidal activity of the crude root extract of Ixora coccinea was carried out. 400g of the plant material each was dried pulverized and extracted with sufficient quantity of water, methanol and acetone separately. The extracts were dried, and used for larvicidal assay. The assay was carried out according WHO, 2005 guideline on larvicidal assay with some modifications. The activity was evaluated using six different concentrations of 0.5,1, 2, 3, 4, and 5mg/ml in volume of 100ml of water. it was run in triplicate with control for each concentration. 20 healthy larvae of 3rd instarwas used for each of the triplicate and the control. The activity was monitored every 24 hours for 3 days. The number of death after every 24 hours was observed and recorded. The percentage mortality and the LC50 were calculated. Examination of the results showed that the acetone extract gave the highest mortality after 72 hours with 100% mortality and LC50 of 0.8mg/ml. The methanol extract gave 51.7%mortality with the highest concentration of 5mg/ml used and LC50 of 4.95mg/ml after 72 hours, while the aqueous extract gave 0%activity with the 5mg/ml highest concentration use after 72 hours. The result of this study showed that the acetone root extract of Ixora coccineacould further be worked on to isolated the active principle(s) with the larvicidal activity.